Motivation as Mediator between the Qualities of Sports Services with the Development of Human Capital of Sports Culture: A Structural Equation Model Analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main purpose of this study was to test the motivation variable as a mediator that correlate the Quality of Sports Services with the development of human capital of sports culture in Sabah. In addition, this study was conducted to identify the influence of exogenous variables on endogenous variables of the studies. This quantitative study used survey method, involving 473 students in Kota Kinabalu. Human Capital Model (Swanson & Holton III, 2001) was used as the basis model for this study. The data were analyzed using path analysis (SEM) via AMOS software. The main findings of the study showed that motivation is the significant mediator between the Sports Service Quality with the Development of human capital of the acculturation of sports in Kota Kinabalu. The analysis of the structural equation model (SEM) also showed that the data in this study fit with the proposed regression model. Hence, the independent variables have direct and indirect relationships with the dependent variable of the study which are the development of human capital of sports culture. It is hoped that this study will provide useful inputs for the improvement of the national education system in sports.